Water Conservation and Dryland Crop Production in Arid and Semi-Arid Regions - Oswal, M C (Annals of Arid Zone, 2016)
In this paper, the work on rain water conservation, harvesting and its appropriate use in dryland crop production, carried out by various dryland centres located in hot arid and semi-arid regions of India receiving annual rainfall up to 750 mm, has been reviewed. The generated technology of water conservation and its productive use is capable of greatly improving and stabilizing dryland crop production. This requires selection of short duration and low water requiring crops/cropping systems, effective moisture conservation measures, establishment of crops under ridge-furrow system and farm pond for harvesting runoff for providing life saving/critical irrigation. Further research is required on refinement of the technology for pond water harvesting and water budgeting under bare and cropped conditions with different crops. For rapid diffusion of the technology costume-hire services for deep tillage, ridge furrow cultivation and recycling of water harvested in farm pond is required.